Precursor concentration-tuned optical and electrochromic performance of sol-gel-derived V2O5 thin-film devices - Thien, Gregory Soon How; Cheng, Zhang Xuan; Tan, Ming Yue; Eldjilali, Cheikh Zakaria; Abdelhamed, Abdelrahman Hamed Ebrahem; Sadeq, Faisal Abdullah; Low, Pei Ling; Tan, Kar Ban; Chan, Kah Yoong (Elsevier, 2026)
Electrochromic (EC) devices have gained significant attention in energy-saving applications, with V2O5 standing out owing to its excellent Li-ion intercalation and multi-color properties compared to the widely used WO3. Nonetheless, no research has addressed the effect of V2O5 concentration on EC performance. Given the rising popularity of V2O5 in EC devices, this observation has indicated a significant research gap that should be addressed. Therefore, this study investigated the performance of V2O5 EC devices with concentrations ranging between 0.02 mol/L and 0.1 mol/L via sol-gel spin coating. Consequently, higher film thickness was observed as the sol-gel concentration increased, as the V2O5 thin films transformed from amorphous to crystalline phases. Increasing grain size with worm-like structures was also observed as the concentration increased. The EC device that balanced between optical modulation (OM), coloration efficiency (CE), and coloring (t c) with bleaching times (t b) was then observed for the ITO/0.08 V2O5/electrolyte/ITO device. This device showcased optimized values for OM (37.11 %), CE (26.53 cm2 C−1), t c (7 s), and t b (14 s). Overall, these findings could provide novel information regarding the correlation of V2O5 concentration and EC device performance. A unique contribution was also presented in this study by demonstrating a direct relationship between the concentration of sol-gel precursors, the evolution of structure, and the EC performance, potentially for large-scale production and energy-efficient smart window technologies.